Positive Psychological Coaching Tools and Techniques: A Systematic Review and Classification - Richter, Stefanie; van Zyl, Llewellyn E.; Roll, Lara C.; Stander, Marius W. (Frontiers in Psychiatry, 2021)
Positive psychological coaching (PPC) has emerged as a popular “paradigm” for practitioners interested in the professional development of people. A recent review consolidated the literature on PPC and produced a 5-phase positive psychological coaching model aimed at facilitating professional growth. However, little is known about practically operationalizing each phase of the coaching process (i.e how to facilitate each phase and which underlying tools and techniques could be employed to do so). This systematic review aims at a) determining which coaching tools and techniques are proposed within the coaching literature and b) classifying the identified tools and techniques into the respective phases of PPC model. The investigation used a two-step approach by conducting a systematic literature review followed by an iterative heuristic classification process. The systematic literature review resulted in 24 peer-reviewed publications on positive psychological coaching, providing 117 different coaching tools that could be condensed into 18 overarching coaching techniques. The iterative process showed that most techniques and tools are useful in at least two phases. Interestingly, experts still vary in opinion on the timing and application of these specific techniques and tools within the positive psychological coaching process.